Staff perspectives on the feasibility of the person-centered care assessment tool (PCC-at) in HIV treatment settings in Ghana: a mixed-methods study - Jessica E. Posner; Henry Tagoe; Amy Casella; Caitlin Madevu-Matson; Malia Duffy; Melissa Sharer; Henry Nagai (HIV Research & Clinical Practice)
Person-centered care (PCC) aims to improve client’s experiences in HIV care while advancing outcomes. This study team developed the PCC assessment tool (PCC-AT) to assess PCC service performance in HIV treatment settings in Ghana. Study objectives aimed to describe the range of PCC-AT scores within and across study facilities and examine the feasibility of PCC-AT implementation in diverse HIV treatment settings. The PCC-AT was piloted at five health facilities providing HIV services among 37 staff. Immediately following each pilot, focus group discussions (FGDs) were conducted to gather feasibility data. Thematic qualitative analysis was conducted on translated FGD transcripts. Across facilities, providers scored highest in the staffing domain, followed by service provision, and direct client support. Time required to implement the PCC-AT averaged 62 minutes. Providers described the tool as well-structured, user-friendly, relevant, reflective of the core PCC delivery elements, and useful in elucidating actions to improve PCC service delivery across domains. The PCC-AT holds potential to strengthen activities that support clients’ broader clinical, mental and psychosocial wellbeing by offering friendly services that attend to each client’s holistic needs while contributing progress towards epidemic control.